Antifungal effect of atorvastatin in comparison with fluconazole on Candida species isolated from patients undergoing head-and-neck radiotherapy (Dental Research Journal)
Background: Head-and-neck radiotherapy can change oral Candida species and lead to the development of refractory oral candidiasis resistant to the commonly prescribed antifungal medications such as fluconazole. Atorvastatin exerts an antifungal effect by inhibiting the synthesis of fungal wall ergosterol and impairing mitochondrial function. This study aimed to compare the antifungal effects of fluconazole and atorvastatin on Candida species isolated from patients undergoing head-and-neck radiotherapy. Materials and Methods: In this clinical in vitro study, swab samples were collected from 33 patients admitted to Isfahan Seyed-O-Shohada Hospital before the onset and 2 weeks after the initiation of radiotherapy. The antifungal effects of fluconazole and atorvastatin were evaluated by the microdilution test according to the Clinical and Laboratory Standards Institute standards, and measuring their minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC). Data were analyzed by the Mann–Whitney U-test and the statistical significance level was considered P < 0.05. Results: The results showed that the MIC24, MIC48, and MFC of fluconazole were significantly lower than those of atorvastatin for Candida albicans, Candida tropicalis, and Candida glabrata both before (P < 0.001 for all) and during (P < 0.001 to P = 0.003) radiotherapy. Conclusion: According to the results, fluconazole has antifungal effects comparable to those of atorvastatin, but in much lower doses. Atorvastatin showed optimal antifungal effects but in doses beyond the clinically applicable threshold.